Ocular Radiation Threshold Projection Based off of Fluoroscopy Time During ERCP. (May 2017) - Garg, Mrinal S; Patel, Pikul; Blackwood, Margaret; Munigala, Satish; Thakkar, Payal; Field, James; Wallace, Dustin; Agarwal, Satty; Aoun, Elie; Kulkarni, Abhijit; Dhawan, Manish; Farah, Katie; et al.
Abstract : OBJECTIVES: Current international guidelines for ocular radiation exposure suggest a threshold of 20 millisieverts (mSv)/year. Although endoscopists wear lead aprons, use of protective eye wear is optional. This study was conducted to analyze the lens radiation exposure during endoscopic retrograde cholangiopancreatography (ERCP) for endoscopists to determine the time of fluoroscopy needed to warrant using lens protection during ERCP. METHODS: ERCP patients were prospectively enrolled. Indications, interventions, fluoroscopy time, dose, and attending ± fellow involvement were recorded. Radiation exposure was collected from body dosimeters and dosimeters placed between the eyes. Cumulative radiation doses were obtained at study completion and averaged over the total fluoroscopy time to determine the mSv/hour exposure. RESULTS: A total of 187 cases were included. Attendings and fellows wore lens dosimeters in 178 and 126 cases, respectively, and body dosimeters in 174 and 128 cases, respectively. Attendings and fellows wore lens dosimeters throughout 15.89 and 11.24 h of fluoroscopy, respectively. The cumulative radiation dose absorbed per lens dosimeters was 5.35 mSv for attendings and 2.55 mSv for fellows. The projected lens absorption by the body dosimeters was 19.03 mSv for attendings and 5.21 mSv for fellows. The hourly fluoroscopy lens exposure was 0.34 mSv/hour for attendings and 0.23 mSv/hour for fellows. CONCLUSIONS: The amount of fluoroscopy hours needed to reach the currently suggested lens threshold limit (20 mSv/year) was 59.41 h for attendings and 88.17 h for fellows. Radioprotective eye wear should be worn by physicians with yearly fluoroscopy times in similarly structured practices that meet or exceed these thresholds.